2019
DOI: 10.1039/c9ra01598a
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-dependant thermally induced nonlinear optical properties of l-ascorbic acid-stabilized colloidal GNPs and GNP–PVP thin films

Abstract: Gold nanoparticle (GNP) colloids stabilized with various concentrations of l-ascorbic acid were synthesized by the chemical reduction method and characterized by UV-Vis spectroscopy, XRD, FT-IR spectroscopy and TEM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Last but not least, it has been demonstrated that solid solutions can downshift UV photons to wavelengths where crystalline silicon photovoltaic solar cells respond more broadly. [16][17][18][19][20][21] Fig. 6.…”
Section: Yb3+ Dopedsrtio3mentioning
confidence: 99%
“…Last but not least, it has been demonstrated that solid solutions can downshift UV photons to wavelengths where crystalline silicon photovoltaic solar cells respond more broadly. [16][17][18][19][20][21] Fig. 6.…”
Section: Yb3+ Dopedsrtio3mentioning
confidence: 99%